PHARMACOECONOMIC ISSUES OF ADALIMUMAB THERAPY IN JUVENILE IDIOPATHIC ARTHRITIS - K. Simpson; N. Marlow; J. Shaw; А. V. Rudakova (Union of pediatricians of Russia, 2012)
Background. Juvenile idiopathic arthritis (JIA) is the most common type of arthritis in children and is associated with reduced quality of life and increased health care costs. Objective. To evaluate the cost effectiveness of the tumour necrosis factor inhibitor adalimumab (ADA) vs. non-biologic therapy for the treatment of JIA in Russian children and adolescents. Materials and Methods. A Markov model was developed on the basis of the DE038 clinical trial, which compared ADA plus methotrexate (MTX) vs. placebo plus MTX for the treatment of JIA in children aged 4-17 years. Cost-effectiveness analyses were performed from the standpoint of the Russian health care system and society as a whole. Base case analyses followed 11-year-old patients with JIA for a period of 7 years (until the age of 18 years) or over an expected lifetime. Additional analyses followed patients aged 7 years at treatment initiation for a period of 11 years or over a simulated lifetime. The cost of treating severe JIA was assumed to be the same as reported in a published investigation. The cost of ADA therapy was based on the expected cost assuming inclusion in the List of Vital and Essential Medicinal Products. This took into account the Value Added Tax and a 10% trade mark-up. Treatment outcomes were measured in quality-adjusted life years (QALYs). Results and Discussion. Over a 7-year time horizon, the incremental cost-utility ratio (ICUR) for ADA vs. conventional nonbiologic therapy in the treatment of JIA in 11-year-old patients was 1,571,500 roubles/QALY when using a health care system perspective and 1,515,000 roubles/QALY when using a societal perspective. Over a simulated patient lifetime, the corresponding ICURs were 286,300 roubles/QALY and 275,300 roubles/QALY, respectively. Over an 11-year time horizon, the ICUR for ADA vs. conventional non-biologic therapy in the treatment of JIA in patients aged 7 years at the start of therapy was 852,400 roubles/QALY when using a health system perspective and 802,900 roubles/QALY when using a societal perspective. The corresponding ICURs were 229,700 roubles/QALY and 215,500 roubles/QALY, respectively, when modeling cost effectiveness over a simulated patient lifetime. In each set of analyses, the ICUR for ADA over conventional therapy declined precipitously when taking the long-term consequences of JIA into account. Conclusions. Relative to conventional non-biologic therapy, ADA is cost effective when used to treat JIA patients whose disease severity is comparable to that of participants in DE038. ICURs estimated in the base case lifetime analyses did not exceed the per-capita gross domestic product (GDP) for the Russian Federation - i. e., approximately 380,000 roubles in 2011- which is regarded as the upper threshold for highly cost-effective interventions. These findings support the use of ADA in clinical practice.